Potensi Isolat Rare Actinomycetes Dari Pasir Pantai Baron Gunung Kidul Yogyakarta Sebagai Antibakteri Terhadap Bakteri Escherichia coli - Zukruf Al Jaelani, Muhammad; , Ratna Yuliani, M.Biotech.St (2016)
The use of antibacterial drugs irrationally leads to bacterial resistance to antibiotic, thus new antibacterial agents are needed. Rare Actinomycetes has potential to produce of biologically active metabolites. This study aimed to obtain rare Actinomycetes isolates from the sand beach of Baron Gunung Kidul Yogyakarta which has potential as antibacteria against Escherichia coli and determine the compound that has antibacterial activity. The study were conducted by pre-treating samples used dry heat at 120°C for 1 hour, then isolation of rare Actinomycetes were done using starch-casein agar, Bennett agar, oatmeal agar, and starch-casein broth media. Identification of isolates were conducted microscopically and macroscopically. Screening of antibacterial activity were performed by agar block method against Escherichia coli. Thin layer chromatography (TLC) and bioautography used silica gel GF254 as stationary phase and n-hexane : ethyl acetate (1:1) as mobile phase. Based on the results, 18 isolates were suspected as rare Actinomycetes. Isolates of rare Actinomycetes with code of 1C was able to inhibit the growth of Escherichia coli with weak potential (diameter of inhibition zone 15 mm). TLC detection results and bioautography showed that the spots at Rf 0.08 and 0.62 has antibacterial activity which suspected as class compounds terpenoids and propylpropanoid.